Administrative Discretion in Emergency Health Services from the Perspective of Administrative Law: Diskresi Pelayanan Kesehatan Darurat dalam Perspektif Hukum Administrasi Negara - Rahmadani, Ruri (Mendapo: Journal of Administrative Law, 2026)
Medical treatment administered in emergency circumstances without the prior consent of the patient or their family constitutes a doctrinal exception to the principle of informed consent as an expression of patient autonomy. Within the framework of Administrative Law, such action shall not be construed merely as a private therapeutic relationship between physician and patient, but rather as the exercise of administrative discretion in the delivery of public health services. This study aims to examine the legal basis of authority, the normative limits of discretionary power, and the construction of administrative liability borne by hospitals in relation to emergency medical interventions performed without consent. This research employs normative legal methodology, applying statutory and conceptual approaches, supported by systematic interpretation and juridical reasoning concerning attribution, delegation, and mandate of authority in the health sector. The analysis is situated within the principles of legality, proportionality, public interest, due care, and accountability as embodied in the general principles of good governance. The findings demonstrate that the legality of emergency medical intervention without consent is justified insofar as it is undertaken to protect life and public interest, complies with professional standards and standard operating procedures, and remains within the lawful scope of delegated authority. Medical discretion is not absolute; it is subject to the prohibition of abuse of power and to institutional accountability mechanisms. Accordingly, hospitals, as public service providers exercising governmental functions in the health sector, shall bear primary administrative responsibility for the use of such discretion, including supervision, documentation, risk management, and corrective measures. Legal protection of patients in emergency settings must therefore be reconstructed within the regime of institutional administrative accountability rather than confined solely to civil or criminal liability.